KRITIK KONSEPTUAL TERHADAP MANAJEMEN PENDIDIKAN INDONESIA - Masti Yanto; Nailatur Rizqiyah; Nisa’el Amala; Selfi Lailiyatul Iftitah (Jurnal Pendidikan Nusantara, 2024)
Education management in Indonesia faces various significant challenges, one of which is conceptual errors in its implementation. This article aims to analyze the misconceptions about educational management that often occur in Indonesia and their impact on the quality of education. The research method used is a literature study by collecting data from various related sources, including journals, books and educational reports. The results of the analysis show that errors in the concept of education management in Indonesia include inaccuracies in planning, organizing, implementing and supervising. This article concludes that serious efforts are needed to correct misconceptions about educational management through increased understanding, training and continuous evaluation. The recommendations put forward include strengthening the education management curriculum, increasing the capacity of teaching staff and managers, as well as implementing policies that are more relevant and contextual.